Digital Marketing dalam Meningkatkan Keunggulan Kompetitif Kerupuk Singkong Desa Petung Kabupaten Gresik: Digital Marketing in Increasing Competitive Advantage “Kerupuk Singkong Ma'yah” Petung Village Gresik District - Has, Dwi Faqihatus Syarifah; Yuliati, Luluk; Wulandari, Dwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The rapid development of technology has an impact on changes in behavior and people’s lives in all sectors. Technological progress cannot be avoided. Therefore, we must be able to use it wisely to support productivity in life, both in the sectors of Government, Culture, Education, and the Economy. The method used in the implementation of community service is ( socialization is carried out by exposing digital marketing materials; (2) education, namely providing an understanding of the importance of labeling on product packaging; (3) training and practice of making labels and Instagram social media for promotion and market product so that the marketing reach os its product is more comprehensive. This community service activity concludes that the socialization, education, training, and practice participants went well and succeeded; the cassava cracker business owner has put a unique name label (Krusava Ma’Yah) on the cracker packaging and has an Instagram @_krusava ma’yah, which was created and made by the trainees. It is hoped that the improvement in the condition of business actors after assistance will be able to increase the competitive advantage of cassava cracker product.